The need for communicate and declaration of acceptance in the law of Iran, the UK and the principles of international commercial contracts (Unidroit) - Reza Maghsoody; Noora Ehsangar (پژوهشنامه حقوق تطبیقی, 2015)
Declaration and announcement of the will and its various forms poses some problems; including if it is necessary that the offeree should be informed about acceptance? In other words, whether Informing the offeree of the acceptance is required for acceptance to take effect and also for contract to occur? Although being informed about acceptance is not a requirement for a contact to occur in the law of Iran; but in the law of England and Unidroit, the general rule is that declaration and communication of an acceptance are the main conditions for an effective acceptance which without them acceptance is not valid and no contact will get form. With regard to this general rule, in case of an offeror not being informed about acceptance, except in exceptional circumstances, such as a unilateral contract, offeror's negligence, communication by post, offer's circumstances and others, no contract will be concluded and as a result no obligation arises for him. Therefore, there are different approaches in different legal systems for announcement and communication of acceptance